Amostragem do ácaro-do-bronzeado Dichopelmus notus Keifer (Acari, Eriophydae) na cultura da erva-mate em Chapecó, Santa Catarina - Vieira Neto, João (2006)
The mate-tea tree it is a forest species that occurs naturally in the tempering regions and subtropical of America of the South. In Brazil it occurs mainly in the states of the Rio Grande do Sul, Paraná and Santa Catarina. Its leaves and branches are used, mainly, as raw material in the preparation of teas. During many years, the exploration of mate-tea if restricted the natives plants, but recently it passed also to be cultivated in monoculture, system that favors the development of pragues. The tan-mite, Dichopelmus notus (Keifer, 1959) (Acari, Eriophydae), specific plague of this culture, that before met in low population levels, currently due to the high infestations, cause the premature leaf fall and death of the tips, with elevated damages to the producers. This mite comes being considered as one of the main pragues of the culture of mate-tea in the Argentine and Brazil. In result of the importance of mate-tea and of the increase of the infestation of this mite, it is necessary to search alternatives and technologies that maximize the profitability of the culture. This work aimed to select a sampling methodology to monitor the levels of infestation of the tan-mite in matetea orchards, destined to explain its habits. The study were carried out in orchard of ten years, in the arrangement of 2,5 X 4,0 m with height of 1,5 m, located in the Chapecó county, Santa Catarina state, Brazil. In three areas of approximately 2,500 m2, distant between itself about 100 m, had been selected 30 plants randomly. Fortnightly, in the period of 27/01/2004 the 10/01/2005, were evaluated infestation of D. notus in 18 mature leaves of ten plants in each area, being six in the upper one-third, six in the medium one-third and six in lower one-third, three in each localization of the crown, external and internal. The evaluations were executed directly in the orchard, using lenses with increase of ten times and 1 cm2 of fixed field. The results had evidenced that: the infestation of the mite occurs of aggregate form; the estimate of the average number of mites for cm2 of leaf, with level of 15% precision, can be carried through in three leaves of 30 plants in sections of hectare, from february to april; the mites concentrate themselves in the external part of the plant in the upper one-third part of canopy as well as at part medium one-third; positive correlation was observed among the population of D. notus and minimum and maximum temperatures, however negative correlations was observed among tan-mite e population and rain precipitation, relative humidity and speed of the wind; the Model of Normal Approach with Correction of Continuity must preferential be used in the elaboration of binomial sequential sampling plans for D. notus.